PENGARUH KARAKERISTIK PERUSAHAAN DAN STRUKTUR KEPEMILIKAN TERHADAP PENGHINDARAN PAJAK / TAX AVOIDANCE PADA PERUSAHAAN BUMN YANG TERDAFTAR PADA BEI TAHUN 2013-2016 - Arviyanti Arviyanti; Enong Muiz (STIE Muhammadiyah Jakarta, 2020)
This study was conducted to determine empirical evidence of the influence of company characteristics and ownership structure on tax avoidance / tax avoidance in state-owned enterprises (SOEs) listed on the Indonesia Stock Exchange (BEI) in 2013-2016. The samples used were 15 companies for 4 years so the total sample of 60 company data. Analysis of the data used is GLS (General Least Square) with the help of Eviews version 9. For independent variables, variable company characteristics are proxied on profitability (Return on Assets / ROA), leverage (Debt to Equity Ratio / DER), company size (Size) , capital intensity (Capital Intensity Ratio / CIR). The ownership structure variable is proxied to managerial ownership (OWNMANAG) and institutional ownership (OWNINS). As for the dependent variable tax avoidance is proxied at the effective tax rate (ETR / Effective Tax Rate). The results of this study are the influence of company characteristics which are proxied on ROA, DER, Size, CIR, only ROA which has a significant negative effect on tax avoidance. DER and Size have no significant negative effect, while and CIR have positive but not significant effect on tax avoidance. Effect of Proposed Ownership Structure on managerial ownership does not have a significant positive effect on tax avoidance and institutional ownership does not have a significant negative effect on tax avoidance